Knesset Attitudes towards Education Issues in IsraelIn the light of the minutes of the Israeli Knesset 1966_ 1967 - ....م .د. جاسم محمد شغيت الكعبي ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2019)
Modern education is one of the pillars of the Renaissance in many countries in the world because of the scientific cadres that help in building society. Our research was based on the Knesset records and official reports published by the Institute for Palestine Studies, which spoke about the Knesset members’ interventions on issues related to the conduct of the educational process.